Constitutionalism, hyper-presidentialism and imbalance of powers in Brazil at the time of the COVID-19 pandemic - Borges de Freitas, Graça Maria (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The coronavirus pandemic is the result of a political and economic model that generates environmental, economic and social degradation, which at the same time, aggravates the crises it generates, producinga vicious circle. Its occurrence revealed structural, political and economic problems, which explained the great challenges that humanity, in general, and Latin America, in particular, need to face in order to overcome the current model. Brazil represents a paradigmatic case for discussing the perverse effects of the political and economic model on democracy and the effectiveness of economic, social, cultural, and environmental rights (ESCR). This is especially true in a country whose institutional design of thethree powers and legal culture do not favour the protection of fundamental rights. This is evidenced by the way in which the pandemic was confronted by an autocratic government. In addition to the difficulties of the powers that be to contain the perverse effects of the abusive practices of the former leader.